Lymphatic filariasis: a snap shot of a neglected tropical disease - Duker, Alfred Allan; Kwarteng, Efiba Vidda Senkyire (International Journal Of Community Medicine And Public Health, 2021)
Lymphatic filariasis (LF) is a leading cause of disability worldwide and one of the most crippling and stigmatizing tropical diseases. LF transmission is widespread throughout regions of West Africa, coastal and south-eastern Africa, East and South-east Asia, South western India, Western Pacific and parts of South and Central America. The disease manifests as disfiguring pathology caused by microfilariae larvae damage to lymph vessels and nodes. LF is spread by mosquitoes that have been infected with filarial nematode larvae and about a billion people in 52 countries are thought to be at risk of contracting the disease on a global scale. Complex immune responses to filaria and their endosymbionts cause the pathologies associated with lymphatic filariasis. Several studies show that non-climatic factors that may be responsible for LF transmission at the micro level include environmental, social, economic, and demographic factors. Currently, the infection is controlled by mass drug administration regimens, vector control strategies and management of morbidities. This review discusses the ecological drivers of lymphatic filariasis transmissions in endemic hotspots.